Perihepatic Packing versus Primary Surgical Repair in Patients with Blunt Liver Trauma; an 8-year Experience - Shahram Paydar; Mojtaba Mahmoodi; Mohammad Jamshidi; Hadi Niakan; Mohammad Keshavarz; Nader Moeenvaziri; Mohammad Esmaeil Ghorbaninejad; Farnaz Farrokhnia; Forough Izadi Fard; Zahra Jaafari; Yalda Golshan; Hamidreza Abbasi; et al. (Bulletin of Emergency and Trauma, 2014)
Objective: To explore the pros and cons of early versus delayed intervention when dealing with severe blunt liver injury with significant hemoperitoneum and hemodynamic instability. Methods: This retrospective cross-sectional study was performed at the Nemazi hospital, Shiraz, Southern Iran, level I trauma Center affiliated with Shiraz University of Medical Sciences. The study population comprised of all patients who were operated with the impression of blunt abdominal trauma and confirmed diagnosis of liver trauma during an 8-year period. All data were extracted from patients’ hospital medical records during the study period. The patients’ outcome was compared between those who underwent perihepatic packing or primary surgical repair. Results: Medical records of 76 patients with blunt abdominal liver trauma who underwent surgical intervention were evaluated. Perihepatic packing was performed more in patients who have been transferred to operation room due to unstable hemodynamics (p<0.001) as well as in patients with more than 1000 milliliters of hemoperitoneum based on pre-operative imaging studies (e.g. CT/US) (p=0.002). Conclusion: We recommend that trauma surgeons should approach perihepatic packing earlier in patients who have been developed at least two of these three criteria; unstable hemodynamics, more than 1000 milliliters hemoperitoneum and more than 1600 milliliters of intra-operative estimated blood loss. We believe that considering these criteria will help trauma surgeons to diagnose and treat high risk patients in time so significant hemorrhage (e.g. caused by dilatational coagulopathy, hypothermia and acidosis, etc.) can ultimately be prevented and more lives can be saved.